2010
DOI: 10.1071/wf07119
|View full text |Cite
|
Sign up to set email alerts
|

Firebrands and spotting ignition in large-scale fires

Abstract: Spotting ignition by lofted firebrands is a significant mechanism of fire spread, as observed in many large-scale fires. The role of firebrands in fire propagation and the important parameters involved in spot fire development are studied. Historical large-scale fires, including wind-driven urban and wildland conflagrations and post-earthquake fires are given as examples. In addition, research on firebrand behaviour is reviewed. The phenomenon of spotting fires comprises three sequential mechanisms: generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
150
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(153 citation statements)
references
References 38 publications
(71 reference statements)
3
150
0
Order By: Relevance
“…A prescient preliminary analysis of 'Santa Ana-like' winds in the Oakland Hills was performed in 1973 [16], some 18 years prior to the Oakland Hills fire of 1991, and analyses [17][18][19] subsequent to that fire confirmed their localization at the eastern San Francisco Bay Area. Some time thereafter, colloquial usage of the term "Diablo winds" by the National Weather Service expanded to include the Bay area in general (Jan Null, personal communication), in agreement with news stories on the October 2017 Northern California firestorm.…”
Section: Introductionmentioning
confidence: 99%
“…A prescient preliminary analysis of 'Santa Ana-like' winds in the Oakland Hills was performed in 1973 [16], some 18 years prior to the Oakland Hills fire of 1991, and analyses [17][18][19] subsequent to that fire confirmed their localization at the eastern San Francisco Bay Area. Some time thereafter, colloquial usage of the term "Diablo winds" by the National Weather Service expanded to include the Bay area in general (Jan Null, personal communication), in agreement with news stories on the October 2017 Northern California firestorm.…”
Section: Introductionmentioning
confidence: 99%
“…These fires overwhelm fire suppression capabilities despite the fact that suppression resource levels and fire crew training are better than ever before (WWF 2006, Cardil et al 2013b). In recent years, not only in the USA, Canada or Australia but also in the Mediterranean basin, extreme fire behavior events have exhibited fire-line intensities, spreading and massive spotting (Koo et al 2010;Molina et al 2010) that have made them resistant to suppression efforts until a change in weather (i.e., wind speed reduction and relative humidity increase) or in fuel load and continuity (Finney 2007;Werth et al 2011). These events have challenged fire risk management activities and policies and revealed the need to integrate fire risk mitigation into landscape management actions, through fire ignition prevention plans and strategies to reduce fuel load and continuity (Fernandes et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The fire impact may be at various intensity levels and may include convective heating or direct contact of the flames, radiant heat flux from nearby flames and airborne firebrands (Cohen 2000;Koo et al 2010;Mell et al 2010). Focusing on the effect of meteorology on fire characteristics, Blanchi et al (2010) analysed the relationship between house loss and the fire weather under which it occurred and found that virtually all of the losses occurred under extreme conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Structure flammability depends on exterior construction materials (e.g. roof type and roof material influence the ignition by firebrands (Koo et al 2010;Gibbons et al 2012)) and construction design (e.g. number, size and characteristics of openings).…”
Section: Introductionmentioning
confidence: 99%